Accelerated degradation of polymer electrolyte membrane fuel cell gas diffusion layers: Performance degradation and steady state liquid water distributions with in operando synchrotron X-ray radiography - Liu, Hang; George, Michael G.; Ge, Nan; Banerjee, Rupak; Chevalier, Stephane; Lee, Jongmin; Shrestha, Pranay; Muirhead, Daniel; Hinebaugh, James; Zeis, Roswitha; Messerschmidt, Matthias; Scholta, Joachim; et al. (ECS Transactions, 2016)
As-received pristine gas diffusion layers (GDLs) were degraded through an accelerated artificial aging process by immersion into a 35% solution of H2O2 at 90°C for 12 hours. Polarization curves were obtained while synchrotron X-ray radiography was performed to investigate the effect of ageing on liquid water transport behavior. Peak output power density of the fuel cell composed of the aged GDL reached only 76% of that of the fuel cell composed of the pristine GDL. This performance degradation was attributed to an increase in mass transport resistance associated with liquid water accumulation at the aged GDL and flow field channel interface. The aged GDLs showed more liquid water accumulation at the microporous layer (MPL)/carbon substrate interface and carbon substrate regions than pristine GDLs at low current density operation. A fully developed water profile was established at lower current density for the aged GDLs compared to pristine GDLs.
CRIS-Team Scopus Importer:2023-08-01